Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).